The Amalgamation of Ecopreneurship, Artistic Orientation and Digital Marketing in Increasing Sustainable Competitive Advantage of Creative Industries: Natural Resource-Based View Theory (NRBV) Perspective - Wilujeng, Gandis; Khouroh, Umu; Natsir, Mokhamad (University of Merdeka Malang, 2024)
This study aims to examine the effect of the artistic orientation of ecopreneurship on competitive advantage and the role of digital marketing in mediating the relationship between artistic orientation and ecopreneurship with competitive advantage. This study was designed using an explanatory research method. The population in this study were MSMEs in the craft sector in Batu City. Respondent data and information were obtained from the Department of Cooperatives, Micro Enterprises, Industry, and Trade. The number of crafts MSMEs was 120 and all of them were used as research samples. Data measurement used a 5-point Likert scale. This study used descriptive and quantitative analysis techniques with the SEM-PLS analysis method. The findings of the study indicate that artistic orientation and ecopreneurship have a major impact on increasing competitive advantage. Digital marketing plays a more dominant role as a mediator than as a moderator in the relationship between artistic orientation and ecopreneurship with competitive advantage. Artistic Orientation, ecopreneurship, and digital marketing create a synergistic effect, positioning companies for sustainable success by aligning their business practices with consumer demands for innovation and sustainability.